Frostbite - Mead, Richelle (London : Penguin Books, 2013)
While on a school skiing trip, guardian-in-training Rose faces everything from misunderstandings between friends to fights among factions of Moroi as reports of horrific Strigoi attacks raise tensions, ultimately leading Rose and some of those closest to her into a battle that teaches her much about life, death, and love.
Young Adult.
Young Adult
Keywords: High schools -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction; Skis and skiing -- Juvenile fiction; Social classes -- Juvenile fiction; Vampires -- Juvenile fiction; High schools -- Fiction; Interpersonal relations -- Fiction; Magic -- Fiction; Schools -- Fiction; Skis and skiing -- Fiction; Social classes -- Fiction; Vampires -- Fiction; High schools -- Fiction; Interpersonal relations -- Fiction; Magic -- Fiction; Occult fiction; School stories; Skis and Skiing -- Fiction; Social classes -- Fiction; Vampires -- Fiction; Occult fiction